A novel approach for modeling MRR in EDM process using utilized discharge energy. (15th February 2023) - Sahoo, Rajesh; Singh, Nirmal Kumar; Bajpai, Vivek
Abstract: The discharge energy generated during the EDM operation characterizes the productivity of the process. The present research attempts to model the material removal process of EDM by obtaining the actual discharge energy during the spark occurrence. The model incorporates the actual discharge conditions by analyzing the real-time V–I waveforms acquired during the EDM operation to determine the discharge power. The model also establishes that discharge power density is a function of applied heat flux and discharge gap. The model verification is conducted by performing a series of experiments on Titanium grade-5 alloy using a full factorial L18 design. The current study implements tool lift time compensation to achieve accurate MRR from the experimental outcomes. The specific energy obtained using the current approach shows better stability compared to previous literature. The parametric studies show gap voltage to be the most significant parameter in influencing the MRR. The main effects plot show the influence of different process parameters on MRR. Additionally, the surface morphology of workpiece and tool surface through SEM and EDS analysis shows the presence of different anomalies and confirms surface alloying. The predicted outcomes of the model show a maximum deviation of 13.05% from the practical evidence. Graphical abstract: Highlights: Numerical modeling of MRR by determining the actual discharge power during EDM operation. Analysis of acquired V–I waveforms to determine the real-time discharge attributes. Determination of discharge power density as a function of heat flux and discharge gap. Determination and comparison of specific energy by implementing utilized discharge energy. Tool lift time compensation has been implemented to acquire MRR from the experimental outcomes.